Phytochemical constituents, advanced extraction technologies and techno-functional properties of selected Mediterranean plants for use in meat products. A comprehensive review. (June 2020) - Alirezalu, Kazem; Pateiro, Mirian; Yaghoubi, Milad; Alirezalu, Abolfazl; Peighambardoust, Seyed Hadi; Lorenzo, Jose M.
Abstract: Background: Antioxidants and antimicrobials are increasingly becoming important additives in meat industry to extent shelf life and increase acceptability. Oxidative changes and microbiological activities have negative effects on the sensory, stability, nutritional and acceptability properties of the meat products. Mediterranean plant extracts and essential oils (EOs) have been studied as potential natural antimicrobials and antioxidant activity added to meat and meat products, as well as medicinal and functional properties. In recent years, plant derivatives are fairly becoming important in minimal processed products because of the high phenolic content, what allows to enhance the color stability and decrease off-flavors. Scope and approach: This review provides recent information of phytochemical components, advanced extraction technologies and phenolic composition of Mediterranean plant extracts and EOs, as well as their antioxidant, antimicrobial, health promotion and sensory properties as natural preservatives in meat and meat products. Key findings and conclusions : A high concentration of phenolic and flavonoid content was observed in microwave assisted extraction (MAE), followed by ultrasound assisted extraction (UAE), conventional solvent extraction, and CO2 extraction. Phenolic acids and terpenoids were usually among the major components of common Mediterranean plant extracts and essential oils, respectively. Rosemary, garlic, lavender, leek, olive leaf, onion, oregano, pepper, peppermint, sage and Satureja montana are most important aromatic Mediterranean plant species used in meat industry and have exhibited similar or better antimicrobial and antioxidant properties than chemical preservatives. Flavonoids have beneficial effects on human and have been linked with the prevention of atherosclerosis, hypertension, dementia, diabetes and thrombosis. Graphical abstract: Image 1 Highlights: Bioactive and functional compounds in Mediterranean plants were characterized. Novel extraction technologies allow to obtain high quality plant extracts and essential oils. Mediterranean plants extracts and essential oils are rich in phenolic compounds. Antimicrobial and antioxidant activity of the extracts and essential oils in meat and meat products. Synergistic interactions between natural and chemical preservatives should be considered.